Problematizando a regionalização da alimentação dentro do programa nacional de alimentação escolar - Siqueira, Luanny da Silveira (2018)
The research developed was aimed at understanding the regionalization of school feeding, based on the understanding and actions of nutritionists of the PNAE and school managers who have contact with the program. Thus, the research proposed to verify, in a comparative way, the main differences between the practice and the legal legislation that establishes the guidelines of the program, taking into account the regionalization of school feeding required by Law 11.947 / 2009. However, the research also aims to identify how the election of food as regional by nutritionists, as well as proposed to investigate how the regionalization of PNAE menus can ideally occur and how it can be put into practice . For this, the study is a qualitative research, since it was used the collection of data through the analysis of bibliographical researches and documents, also anchored in interviews in order to better understand the processes performed in the execution of the PNAE. Therefore, the results of the research showed that one of the main obstacles that PNAE faces is the inadequacy of meals served to the eating habits of schoolchildren. This is mainly due to the lack of regionalization of the menus, an action that when performed takes place superficially and simplistically, not representing the taste and desire of the students. In addition, the research revealed that in the PNAE there is a shortage of professionals and equipment that make it impossible to carry out effective and precise work throughout the development of activities. Thus, it is evident that these and other problems corroborate to reinforce the distance between the theory and practice of PNAE.